Conversor isolado de alto ganho com baixa ondulação de corrente de entrada e de saída para aplicações em sistemas fotovoltaicos - Pontes, Anderson Paulino (2022)
This work proposes a c.c.-c.c converter topology. high gain for applications in photovoltaic systems connected to microgrids and nanogrids. The presented topology aims to obtain low ripple current source characteristics at the input and output of the converter, to respectively satisfy the maximum power point tracking (MPPT) and avoid the "knocking phenomenon" in the d.c. bus, which can generate interference, impair control and interfere with the bus. Galvanic isolation aims to meet the safety standards established in some countries for photovoltaic systems. The work presents the theoretical foundation that shows some techniques for obtaining high gain that were used in the converter, then the steps of operation of the converter are presented, the equations of each step and finally the qualitative and quantitative analyses, making a comparison between simulation and experimental results. The prototype built to validate the theoretical project was developed to support a power of 390 W, with an output voltage of 380 V and presented a maximum efficiency of 91.76%, validating the proposal.